Performance evaluation of respiratory motion‐synchronized dynamic IMRT delivery. (6th May 2013) - Yoganathan, S.A.; Das, K.J. Maria; Agarwal, Arpita; Kumar, Shaleen
Abstract : The purpose of this study was to evaluate the capabilities of DMLC to deliver the respiratory motion‐synchronized dynamic IMRT (MS‐IMRT) treatments under various dose rates. In order to create MS‐IMRT plans, the DMLC leaf motions in dynamic IMRT plans of eight lung patients were synchronized with the respiratory motion of breathing period 4 sec and amplitude 2 cm (peak to peak) using an in‐house developed leaf position modification program. The MS‐IMRT plans were generated for the dose rates of 100 MU/min, 400 MU/min, and 600 MU/min. All the MS‐IMRT plans were delivered in a medical linear accelerator, and the fluences were measured using a 2D ion chamber array, placed over a moving platform. The accuracy of MS‐IMRT deliveries was evaluated with respect to static deliveries (no compensation for target motion) using gamma test. In addition, the fluences of gated delivery of 30% duty cycle and non‐MS‐IMRT deliveries were also measured and compared with static deliveries. The MS‐IMRT was better in terms of dosimetric accuracy, compared to gated and non‐MS‐IMRT deliveries. The dosimetric accuracy was observed to be significantly better for 100 MU/min MS‐IMRT. However, the use of high‐dose rate in a MS‐IMRT delivery introduced dose‐rate modulation/beam hold‐offs that affected the synchronization between the DMLC leaf motion and target motion. This resulted in more dose deviations in MS‐IMRT deliveries at the dose rate of 600 MU/min. PACS numbers: 87.53.kn, 87.56.N‐